"We Need People to be Woken Up and See This!" Teens Learning Through Critical Analysis. Issue 1 (17th December 2021) - Evans, Sarah A.
Abstract: The continued dearth of realistic, culturally diverse characters in children's literature corresponds with the lack of diversity among those who create, publish, and review books. To address this problem, the researcher collaborated with six culturally diverse high school aged girls for a participatory action research (PAR) project that involved critical analysis of children's picture books that mirrored one or more facets of each girl's identity, with an eye to authenticity. The girls concluded that (1) omitting relevant details about a character's identities created cognitive dissonance for the reader, and (2) book creators who choose this approach create potential for cultural outsiders to glean inaccurate ideas. The positive impact on the participants included changes in their relations and/or changes in their thinking. When the project ended sooner than expected and with a different end product, the researcher's own thinking changed about measuring the success of a PAR project.